Hubungan Pola Asuh Ibu Dengan Perkembangan Anak Usia 4-5 Tahun Di Pendidikan Anak Usia Dini (PAUD) Gembira Loka Denpasar Utara Tahun 2018 - I Gst A.A Cahyaningrum A; Ni Luh Putu Sri Erawati; Ni Nyoman Suindri (Poltekkes Kemenkes Denpasar, 2020)
Child development cases are often underestimated and hidden for many people that because not many people know or have not been socialized to the general public. Many children grow up and their behavior does not match their age. The interaction of the child with the mother is the most effective interaction to establish closeness with the child in guiding and controlling the child's behavior. This research aims to determine the relationship of mother’s parenting styles with child development of 4-5 years old children in PAUD Gembira Loka. This research uses cross sectional approach with 42 respondents. The sampling technique is total sampling. Bivariate analysis using fisher exact test. The results showed that 85.7% democratic parenting syle, 14,3% authoritarian parenting style, development of children 83.3% appropriate, and 16.7%. with the result of doubtful. The results of Fisher Exact Test p=0,048 (p0,05) indicate that there is a significant correlation between mother’s parenting style with child development aged 4-5 years in PAUD Gembira Loka. Parents are expected to be able to choose the type of parenting in their children according to the stage and environmental conditions.